Physics-based simulation models for EBSD: advances and challenges. Issue 1 (January 2016) - Winkelmann, A; Nolze, G; Vos, M; Salvat-Pujol, F; Werner, W S M
Abstract: EBSD has evolved into an effective tool for microstructure investigations in the scanning electron microscope. The purpose of this contribution is to give an overview of various simulation approaches for EBSD Kikuchi patterns and to discuss some of the underlying physical mechanisms.